Behavioral and Pharmacokinetic Profile of Indole-Derived Synthetic Cannabinoids JWH-073 and JWH-210 as Compared to the Phytocannabinoid Δ9-THC in Rats - Uttl, Libor; Szczurowska, Ewa; Hájková, Kateřina; Horsley, Rachel R.; Štefková, Kristýna; Hložek, Tomáš; Šíchová, Klára; Balíková, Marie; Kuchař, Martin; Micale, Vincenzo; Páleníček, Tomáš (Frontiers in Neuroscience, 2018)
Synthetic cannabinoid compounds are marketed as ‘legal’ marijuana substitutes, even though little is known about their behavioral effects in relation to their pharmacokinetic profiles. Therefore, in the present study we investigated the behavioral effects of systemic treatment with the two synthetic cannabinoids JWH-073 and JWH-210 and the phytocannabinoid Δ9-THC on locomotor activity and anxiety-like phenotype (in the open field) and sensorimotor gating (measured as prepulse inhibition of the acoustic startle response; PPI ASR), in relation to cannabinoid serum levels. Wistar rats were treated with either JWH-073 (0.1, 0.5 and 5 mg/kg), JWH-210 (0.1, 0.5 and 5 mg/kg), Δ9-THC (1 and 3 mg/kg) or vehicle (oleum helanti) in a volume of 0.5 ml/kg administered subcutaneously (sc.). 60 min after the treatment they were tested in the open field and in the PPI ASR test. Although synthetic cannabinoids, Δ9-THC and its metabolites were detected in the serum after sc. administration, they partially affect locomotor activity but not sensorimotor gating. Furthermore, Δ9-THC (3 mg/kg) induced an anxiolytic-like effect as suggested by the increased time spent in the center of the open field (p<0.05). Our results further support potentially anxiolytic-like effects of pharmacological modulation of the endocannabinoid system.